GE_GERICHTE C/8568/2012 vom 20. Dezember 2013 - GE Cour de justice (2013)
DROIT DU TRAVAIL; INCAPACITÉ DE TRAVAIL; ALLOCATION DE MATERNITÉ; PERTE DE GAIN; VACANCES; AMENDE; SALAIRE | CPC.128.3; CPC.311; CO.322.1; CO.327a.1; CO.324a.1; CO.329d.2; CO.339.1; LAPG.16b à 16f; CO.322b.1; CO.322b.2